Evaluation of fungitoxicants against Alternaria alternata causing umbel blight disease of kala zeera (Bunium persicum) - BADRI*, Z.A. (Indian Phytopathology, 2013)
Six fungitoxicants both systemic (hexaconazole 5EC, myclobutanil 10WP & carbendazim 50WP @ 200, 300 & 400 ppm) and non-systemic (mancozeb 75WP, copper oxychloride 50WP & captan 50WP @ 2000, 3000 & 4000 ppm) were evaluated in vitro against Alternaria alternata (causing umbel blight disease of Kala zeera). Hexaconazole 5EC @ 300 & 400 ppm proved highly superior amongst the systemic fungitoxicants inhibited spore germination and mycelial growth of A. alternata while amongst non-systemic, mancozeb 75WP @ 3000 & 4000 ppm exhibited complete inhibition against the pathogen. In vivo evaluation of fungitoxicants revealed that hexaconazole 5EC @ 300 and 400 ppm was most effective in reducing the disease incidence (8.76 and 6.24 %) compared to control (31.72 %).